Factors Associated With Worsened Neurological Outcomes in Traumatic Subarachnoid Hemorrhage. (1st September 2019) - Xu, Risheng; Xia, Yuanxuan; Vo, Chau D; Yang, Wuyang; Liew, Jason A; Alban, Ted; Feghali, James; Caplan, Justin M; Tamargo, Rafael J; Huang, Judy
Abstract: INTRODUCTION: Patients are often admitted for observation due to isolated traumatic subarachnoid hemorrhage (tSAH). However, factors that are associated with worsening neurological outcomes are unclear. METHODS: Patients who presented with tSAH from January 2017 to May 2017 to our ED were identified. Initial patient characteristics on presentation associated with a neurological decline, neurosurgical intervention, hospital readmission, or death were identified via univariate and multivariate regression. Of note, we did not include patient characteristics that are not available on initial evaluation. We then tested this model by identifying those without risk factors and reported their outcome. RESULTS: A diagnosis of intracranial hemorrhage was identified in 401 consecutive patients over 5 mo, of which 165 (41.1%) had tSAH. On univariate analysis, patient characteristics associated with a neurological decline, neurosurgical intervention, hospital readmission, or death included depressed skull fractures ( P = .02), GCS < 13 ( P < .001), cranial nerve palsies ( P = .01), any disorientation to self, place, or time ( P < .001), concomitant epidural ( P = .027) or acute subdurals ( P < .001), the presence of midline shift ( P < .001), and INR > 1.5 ( P = .03). On multivariate analysis, disorientation [odds ratio (OR): 3.53 (1.24-10.0), P = .018] and the presence of midline shift [OR: 6.8 (1.87-24.66), P = .003] were associated with worsened neurological outcomes. Out of the 165 patients, 104 patients had one or more risk factors, and 44 experienced worsened neurological outcomes; 61 patients did not have any of the above risk factors, and 0/61 (0%) experienced a neurologic decline, intervention, hospital readmission, or death. This corresponds to a test sensitivity of 100%, specificity of 50.4%, and a negative predictive value of 100%. CONCLUSION: Patients with tSAH who are fully oriented and who do not have a midline shift on initial head computed tomography (CT) are less likely to have a neurological decline, require neurosurgical intervention and hospital readmission, or have mortality. Although the presence of risk factors alone does not necessitate worsened outcomes, patients without any risk factors are unlikely to have a neurological decline.